The effect of the use of omeprazole versus famotidine on the kidney transplant function: a randomized controlled study - Miłosz Miedziaszczyk; Marek Karczewski; Ilona Idasiak-Piechocka (Scientific Reports)
Abstract Tacrolimus is metabolized in the liver with the participation of cytochrome P450 isoforms 3A4 and 3A5 (CYP3A4, CYP3A5). Omeprazole, unlike famotidine, is a substrate and inhibitor of CYP2C19, CYP3A4, CYP3A5 enzymes. The aim of the study is to compare the effect of omeprazole and famotidine on the tacrolimus concentration and the kidney transplant function. A randomized study was conducted in 24 adult patients with stable kidney transplant function who received a standard triple immunosuppression regimen. Patients were assigned to the group I (n = 12) additionally receiving omeprazole (20 mg) or the group II (n = 12) receiving famotidine (20 mg). At the time of qualification and during follow-up visits, tacrolimus blood concentration and selected laboratory tests were performed. Statistical analysis was performed using the MedCalc system. The value of tacrolimus concentration in the blood increased after a year in the group I (7.27 ± 2.33 vs 9.20 ± 2.46 ng/mL, p = 0.0478). A reduction in tacrolimus dosage was observed after three years in the group I (3.56 ± 1.75 vs 2.78 ± 1.00 mg, p = 0.0440) and in the group II (2.72 ± 0.84 vs 2.10 ± 0.48 mg, p = 0.0051). There was significant difference in the percentage changes of glomerular filtration rate between the groups after 3 years of the study (− 5.56% vs 9.13%, p = 0.0343). Omeprazole significantly change the concentration of tacrolimus in the blood when administered together with tacrolimus after one year of observation. There was no effect of famotidine or omeprazole on the function of the kidney transplant. ClinicalTrials.gov identifier: NCT05061303.